Results orientated cause marketing: the secrets of effective partnerships in corporate philanthropy - Adler, Stephen M.; Leighton, Hallie (Henry Stewart Talks, 2009)
Benefits of cause related marketing, Consumer, corporate and social investment trends, Checklist for success, Case studies, Celebrity involvement, Do's and don'ts